Development of the flexible- manufacturing-system model for the furniture industry / Ahmed Jaffar and Nor Hayati Saad (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2007)
Rapid changes in technology and consumer demands are challenging the economic viability of fixed production lines. The manufacturing industry must become more flexible and able to quickly respond to changes in the market. Computational technology makes this possible. This report will show that the use of the Flexible-Manufacturing-System (FMS) model will greatly help meet these new challenges. The adaptation of FMS to other industries will serve to facilitate changes affecting choices for consumers, the nature of work, and the fortune of companies. The research presented in this report shows that the furniture manufacturing industry would benefit the greatest from adopting the FMS model in Malaysia. The findings of this paper are based on a case study carried out on a local furniture manufacturing company in Selangor, Malaysia. An FMS simulation was built (using Quest software) to evaluate the industry's performance capability. This model is used to examine the effectiveness of manufacturing operation systems for small and medium-sized industries with the goal of improving it.